Industry Participation in Forming Skilled Workforce through Educational Cooperation and Vocational Training in SMK - Yoto (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Abstract— Education in Vocational High School (SMK/Sekolah Menengah Kejuruan) aims to prepare students to enter the workplace and develop a professional attitude, creative, adaptive and productive. Industry is an important part in helping schools to improve the quality of education, because the industry is the user of graduate who formed through vocational institutes. This study used a qualitative approach with case study method. To determine the validity of the data triangulation of data collection and triangulation of data sources is used. The results showed that in order to prepare mid-level skilled workers in mechanical engineering SMKN 3 Boyolangu Tulungagung form a class of cooperation with PT GMI Chevrolet. Such cooperation includes educational planning, curriculum synchronization, and organized learning. Implementation of learning is implemented in schools and industry working practices in PT GMI Chevrolet. Graduates of the of direct cooperation class recruited into technicians by PT GMI Chevrolet placed on dealers in the province of East Java.